'ÖTEKİ'NE AŞK ya da BİR MAZİDE KALIŞ HİKÂYESİ: GÜL MEVSİMİDİR - (:unkn) unknown (My University, 2015)
İlkçağdan bugüne insanın var olduğu her yerde mutlaka bir ötekileştirme söz konusu edilir. Türk edebiyatının önemli hikâyecilerinden Füruzan, eserlerinde sosyal gerçekçiliği esas alır; toplum içindeki eşitsizliği ve adaletsizliği çoğunlukla ironik bir anlatımla eleştirir. Gül Mevsimidir adlı uzun hikâyesinde de burjuvazinin ötekileştirdiği yoksul kesime bakışını eleştirir. Hikâyede Rüştü Şahin adlı yoksul bir kişiye âşık olan burjuva Mesaadet ve ailesinin şahsında, burjuva kesimin ötekileştirdiği yoksul kesime bakışı ironik bir anlatımla yansıtılır. Hikâyenin ana kişisi yaklaşık yetmiş yaşında olan Mesaadet, hâlihazırda değil hep mazide yaşar. Mazi onun için bir sığınak işlevi görür. Millî Mücadele'de şehit olan sevgilisi Rüştü Şahin'i hayatı boyunca unut(a)maz, başkasıyla evlense de gönlünde hep o yaşar. Mazideki acı-sevinç karışık anıları, onu üzdüğü gibi onun için teselli de olur. Oldukça karmaşık bir ruh hâli içinde olan Mesaadet, ötekileştirdiği/küçümsediği kesime ait Rüştü Şahin'i hem küçümser, hem de ona hayrandır; ona ait anılarını hatırlarken bir yandan öfkelenirken bir yandan da mutlu olur. Bu makalede, maziye sığınan Mesaadet'in genç kızlıktan yaşlılığa uzun bir süreçte yaşadığı çatışmaları, "ötekine bakış", "ötekine aşk", "ötekine yüklenen millî görev" ekseninde değerlendirilmiştir

Since ancient times, in everywhere that human being existed, there is absolutely an otherization discussion. Füruzan, one of the prominent story writers of Turkish literature, bases her works on social reality, and she criticizes mostly with an ironic style inequality and injustice in society. In her long story entitled Gül Mevsimidir, she criticizes the view of bourgeoisie to the poor whom they have otherized. In the story, the view of bourgeoisie to the poor whom they have otherized is reflected with an ironic way in the person of Mesaadet the bourgeois, who loves a poor man named Rüştü Şahin, and her family. Seventy-year old Mesaadet, who is the protagonist of the story, lives in the past, not in the present. The past functions as a shelter for her. She never forgets for the life her beloved Rüştü Şahin, who was martyred in the Turkish War of İndependence, and even though she married with someone else, Rüştü Şahin always lives in her heart. Her bitter-sweet memories sadden her; also she finds solace in them. Mesaadet, who is in a quite confused mood, both despises Rüştü Şahin as a person of the otherized mass and admires to him. While she becomes happy, on one hand, when she remembered the memoires of him, on the other hand she gets angry. In this paper, the conflicts from young girlhood to old age of Mesaadet, who takes shelter in the past, were examined in terms of "view to the other", "love to the other" and "national duty that is put on the other"
LOVE TO THE 'OTHER' OR A STORY OF BEING REMAINED IN THE PAST: GÜL MEVSIMIDIR [IT IS ROSE TIME]
Keywords: Tarih